The Influence of Financial Literacy, Education Level, Financial Attitude, and Personality on Financial Management Behaviour - Prakoso, Adam Saman; Parhusip, Austin Alexander; Wijaya, M. Rizky (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
This study aims to analyze the influence of financial literacy, education level, financial attitude, and personality on the financial management behavior of Micro, Small, and Medium Enterprises (MSMEs) in Medan City. This study uses a quantitative approach with a survey method on 30 MSME respondents and data analysis using multiple linear regression. The results of the study indicate that partially only the financial literacy variable has a positive and significant effect on financial management behavior. Meanwhile, the variables of education level, financial attitude, and personality do not show a significant effect individually. However, simultaneously the four variables have a significant effect on financial management behavior, with a coefficient of determination of 55%. This finding shows the importance of increasing financial literacy as a primary strategy to strengthen financial management practices in MSMEs. This study recommends the development of an applicable and easily accessible financial training program to improve the financial performance of the MSME sector in a sustainable manner.